PERNIKAHAN PADA GELAHANG : SOLUSI KULTURA UNTUK PASANGAN ANAK TUNGGAL DI BALI - Suarsa, Agus Wisnuwardhana; Oktavia, Widya; Silaban, Kenjiro Adriano (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This paper aims to analyze the legal implications of the Perkawinan Pada Gelahang (bilateral marriage) from the perspective of positive law. The main issue lies in the perceived injustice in inheritance distribution. The research question addresses the legal consequences arising from this marriage practice in terms of spousal status, inheritance rights, and child protection. This article adopts a normative approach, utilizing primary legal sources such as Law Number 1 of 1974 on Marriage, along with relevant academic journals as secondary legal materials. The study concludes that Perkawinan Pada Gelahang is conducted in accordance with Hindu teachings, wherein both husband and wife bear dual responsibilities: Niskala obligations, which involve religious ceremonies at both families’ temples, and Sekala obligations, which refer to social duties in each of the spouses’ Desa Pakraman (customary villages). From the standpoint of positive law, legal issues emerge—particularly regarding inheritance—since both spouses are considered equal, with neither being dominant in terms of